Модель синхронного генератора с гладким якорем - Сипайлов Г. А. Геннадий Антонович; Лоос А. В. Александр Владимирович; Хорьков К. А. Константин Александрович; Кулаков В. Ф.; Хорькова В. З.; Андреев В. И.; Баклин В. С. Валерий Сергеевич (1973, 1973)
Заглавие с титульного листа